2015
DOI: 10.3389/fmicb.2015.00001
|View full text |Cite
|
Sign up to set email alerts
|

One Juliet and four Romeos: VeA and its methyltransferases

Abstract: Fungal secondary metabolism has become an important research topic with great biomedical and biotechnological value. In the postgenomic era, understanding the diversity and the molecular control of secondary metabolites (SMs) are two challenging tasks addressed by the research community. Discovery of the LaeA methyltransferase 10 years ago opened up a new horizon on the control of SM research when it was found that expression of many SM gene clusters is controlled by LaeA. While the molecular function of LaeA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

56
1,059
11
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 913 publications
(1,128 citation statements)
references
References 45 publications
56
1,059
11
2
Order By: Relevance
“…Similar to our finding, the induced expression of PR1 was observed by VCs emitted by Paenibacillus polymyxa E681 and T. asperellum IsmT5 and by specific compounds (e.g. tridecane, m -cresol and methyl benzoate) (Lee et al 2012; Naznin et al 2014; Kottb et al 2015). However, our analysis of VCs produced by these F. oxysporum strains did not reveal the production of these compounds (Bitas et al 2015), suggesting the involvement of different compounds in activating the expression of PR1 .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to our finding, the induced expression of PR1 was observed by VCs emitted by Paenibacillus polymyxa E681 and T. asperellum IsmT5 and by specific compounds (e.g. tridecane, m -cresol and methyl benzoate) (Lee et al 2012; Naznin et al 2014; Kottb et al 2015). However, our analysis of VCs produced by these F. oxysporum strains did not reveal the production of these compounds (Bitas et al 2015), suggesting the involvement of different compounds in activating the expression of PR1 .…”
Section: Resultssupporting
confidence: 89%
“…Previous studies reported that VCs emitted by several plant growth promoting fungi, including Ampelomyces sp., Cladosporium sp. and Trichoderma sp., reduced disease symptoms through the activation of signalling pathways that involve SA and JA/ET (Naznin et al 2014; Kottb et al 2015). However, Ryu et al (2004) reported that ISR elicited by VCs emitted by B. amyloliquefaciens GB03 was mediated by ET signalling but did not require the SA or JA signalling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Amplification was performed with a two‐step barcoding approach according to Herbold and colleagues, 2015. In the first‐step PCR, 16S rRNA genes of all Bacteria were amplified with forward primer S‐D‐bact‐0341‐b‐S‐17 (5‐CCTACGGGNGGCWGCAG‐3′) and reverse primer S‐D‐bact‐0785‐a‐A‐21 (5‐GACTACHVGGGTATCTAATCC‐3′), which also contained head adaptors (5′‐GCTATGCGCGAGCTGC‐3′).…”
Section: Methodsmentioning
confidence: 99%
“…To determine the effects of deformability on focusing, a suspension of cyanobacterium Synechocystis sp. PCC 6803, with a typical size of 2 µm42 was introduced into a microfluidic chip with a 4 mm long serpentine section. The cyanobacteria used here have been modified to express green fluorescent protein (GFP) 43…”
Section: Resultsmentioning
confidence: 99%